1997
DOI: 10.1074/jbc.272.14.8895
|View full text |Cite
|
Sign up to set email alerts
|

A 65-kDa Protein Mediates the Positive Role of Heme in Regulating the Transcription of CYP2B1/B2 Gene in Rat Liver

Abstract: Heme deficiency precipitated by CoCl 2 administration to rats leads to a striking decrease in the inducibility of CYP2B1/B2 mRNA levels and its transcription by phenobarbitone (PB), besides decreasing the basal levels. Exogenous hemin administration counteracts the effects of CoCl 2 administration. The binding of nuclear proteins to labeled positive cis-acting element (؊69 to ؊98 nucleotides) in the near 5-upstream region of the gene is inhibited by CoCl 2 administration to saline or PB-treated rats, as assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…The mechanism by which impaired heme synthesis decreases CYP expression is not completely understood and is still the subject of some controversy. Several reports demonstrate that heme stabilizes the mRNA of target genes and is therefore required for effective gene transcription, e.g., for CYP1A1, CYP2B1/2 and HO-1 (Kloepper-Sams and Stegeman, 1994;Sultana et al, 1997;Alam et al, 2003). Consistent with these studies, we speculate that heme deficiency may lead to impaired CYP1A1 mRNA stability, which results in reduced gene transcription.…”
Section: Discussionsupporting
confidence: 77%
“…The mechanism by which impaired heme synthesis decreases CYP expression is not completely understood and is still the subject of some controversy. Several reports demonstrate that heme stabilizes the mRNA of target genes and is therefore required for effective gene transcription, e.g., for CYP1A1, CYP2B1/2 and HO-1 (Kloepper-Sams and Stegeman, 1994;Sultana et al, 1997;Alam et al, 2003). Consistent with these studies, we speculate that heme deficiency may lead to impaired CYP1A1 mRNA stability, which results in reduced gene transcription.…”
Section: Discussionsupporting
confidence: 77%
“…We believe that the heme effect is isoform-specific. Besides CYP1A1, several other P450 isoforms are affected by the availability of heme, like CYP2A5, CYP2B1/2 and HO-1 [54,[56][57][58]. However, CYP2B10, and other hemoproteins, namely neuronal nitric oxide synthase and soluble guanylate cyclase, are reported to function normally with limited heme [54].…”
Section: Availability Of Heme Is Essential For Brain P450 Functionmentioning
confidence: 99%
“…It was reported that the heme moiety stimulated the transcription of the CYP2B1/2B2 gene, and that an unknown 65-kDa protein mediated the role of heme in this stimulation of CYP2B1/2B2 gene transcription. 22) At present, we cannot ignore the possibility that ascorbic acid deficiency might suppress the transcription of the CYP2B1/2B2 gene in liver by reducing cellular heme content. As still another possibility, the mechanism that ascorbic acid deficiency induce HO-1 gene expression might also cause the repression of CYP2B1/2B2 expression.…”
Section: Discussionmentioning
confidence: 99%